Attention should be emphasized to the diagnosis and treatment of functional neurological disorder - WANG Jin⁃tao; LIN Guo⁃zhen; WANG Gang (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Functional neurological disorder (FND) is a kind of autonomic motor or sensory system disease with well⁃defined clinical symptoms. It has attracted the attention of many scientists due to its high incidence and heavy social burden, and many studies have promoted the development of FND. However, due to the late start of related research in China, clinicians, patients and their families have relatively weak understanding of the concept of FND and related knowledge. This article analyzes the current status of FND diagnosis and treatment in China, proposed the suggestions to improve the level of diagnosis and treatment for FND in details and enhance related study.